WORKSHOP ACADEMIC WRITING UNTUK MENINGKATKAN REGULASI DIRI DALAM BELAJAR: WORKSHOP ACADEMIC WRITING UNTUK MENINGKATKAN REGULASI DIRI DALAM BELAJAR - Mahkamah Brantasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2022)
The Pg Early Childhood Study Program, UWGM Samarinda, in November 2021, held an Academic Writing Workshop with the aim of improving students' skills in writing scientific thesis and articles. With this activity, it can make it easier for students to pour their ideas and thoughts into writing, and students no longer feel awkward and anxious when completing their final assignments. And from the Academic Writing workshop, it is expected that students will be able to plan, design, organize and organize writing activities so that students can complete their thesis according to the set time. In the implementation of the online Academic writing Workshop using the Zoom application, the first thing to do is to form a committee that involves students and lecturers, the lecturers as the planning team as well as resource persons, while the students as implementers. The Academic Writing Workshop ran smoothly without any significant problems, thanks to the help of the students as the event organizing committee. With the Academic Writing Workshop, it is hoped that students can use it well so that self-regulation in learning can be at the level and final project, namely thesis, can be completed properly and on time.